TANGGUNG JAWAB NOTARIS DALAM PENGGUNAAN GOOGLE MAPS UNTUK PENCANTUMAN ALAMAT KANTOR SEBAGAI PROMOSI SECARA TIDAK LANGSUNG DITINJAU BERDASARKAN KODE ETIK NOTARIS - Pandi Septiawan; Putra Hutomo; Yuliana Setiadi (Journal of Innovation Research and Knowledge, 2025)
In article 3 paragraphs (8) and paragraph (9) of the Notary Code of Ethics, it is stated that in carrying out their office, notaries are required to have an office and put up a name plate with the aim of making it easier for people who need the services of the notary. With advances in technology, not a few notaries also have office addresses listed digitally, usually using the Google Maps application. The problem formulation in this research is how the position of the notary's office address on Google Maps as a form of promotion is indirectly reviewed based on the notary's code of ethics and what the notary's legal responsibilities are for the office address listed on Google Maps. The theories used in this research are the Technology Utilization Theory according to Haag & Ken and the Legal Responsibility Theory according to Hans Kelsen.The method used in this research is a type of normative juridical legal research, namely secondary data research or law literature only supported by interviews. The research approaches used are the statutory approach, conceptual approach, analytical approach and case approach. The technique for collecting legal materials is carried out by identifying and investing in positive legal rules, researching library materials (books, scientific journals, research reports), and other sources of legal materials that are relevant to the legal issues being studied. The legal materials that have been collected are then classified, selected and ensured that they do not conflict with each other, to facilitate legal analysis and construction.From the research results, it can be concluded that notaries are also required to carry out everything in their official duties guided by their professional code of ethics. Therefore, the notary's actions in using Google Maps can be assessed as an action with a motive to promote himself indirectly.